Modeling urban quality of life with data envelopment analysis methods - Ho, Chin Siong; Muhd. Hussein, Muhammad Zaly Shah (Faculty of Built Environment, 2008)
The research examines the use of Data Envelopment Analysis (DEA) for the measuring performance of the urban quality of life in Malaysia using the CCR model. The Data Envelopment Analysis uses the general purpose linear programming version multi-input multi-output model for the estimation taking the selected cities as the decision making unit (DMUs). The performance measurement of the urban quality of life indicators based on seven (7) sectors out of eleven (11) sectors for better urban environment shows that Melaka city is the most efficient city compared with the others. The analysis result also showed that the two (2) significant sectors that influencing the urban quality of life are demography and land use sectors. From this analysis, the frontier cities indicate that the DEA method seems to be suitable for generating benchmarks for non-efficient cities. As a consequence, the reference city may be used as a stimulation for the other cities to improve their performances.